Burden of vaccine-preventable pneumococcal disease in hospitalized adults: A Canadian Immunization Research Network (CIRN) Serious Outcomes Surveillance (SOS) network study. Issue 29 (22nd June 2017) - LeBlanc, Jason J.; ElSherif, May; Ye, Lingyun; MacKinnon-Cameron, Donna; Li, Li; Ambrose, Ardith; Hatchette, Todd F.; Lang, Amanda L.; Gillis, Hayley; Martin, Irene; Andrew, Melissa K.; Boivin, Guy; et al.
Highlights: Active CAP and IPD surveillance was conducted in hospitalized adults since 2010. Severe outcomes and mortality is seen with CAP and IPD in hospitalized adults. The serotype distribution suggests most disease in adults is vaccine-preventable. The incidence of vaccine-preventable pneumococcal CAP by age was estimated. Most vaccine-preventable pneumococcal disease is seen in adults aged ≥50 years. Abstract: Background: Pneumococcal community acquired pneumonia (CAPSpn ) and invasive pneumococcal disease (IPD) cause significant morbidity and mortality worldwide. Although childhood immunization programs have reduced the overall burden of pneumococcal disease, there is insufficient data in Canada to inform immunization policy in immunocompetent adults. This study aimed to describe clinical outcomes of pneumococcal disease in hospitalized Canadian adults, and determine the proportion of cases caused by vaccine-preventable serotypes. Methods: Active surveillance for CAPSpn and IPD in hospitalized adults was performed in hospitals across five Canadian provinces from December 2010 to 2013. CAPSpn were identified using sputum culture, blood culture, a commercial pan-pneumococcal urine antigen detection (UAD), or a serotype-specific UAD. The serotype distribution was characterized using Quellung reaction, and PCR-based serotyping on cultured isolates, or using a 13-valent pneumococcal conjugate vaccine (PCV13) serotype-specific UAD assay. Results and conclusions: In total, 4769 all-cause CAP cases and 81 cases of IPD (non-CAP) were identified. Of the 4769 all-cause CAP cases, a laboratory test for S. pneumoniae was performed in 3851, identifying 14.3% as CAPSpn . Of CAP cases among whom all four diagnostic test were performed, S. pneumoniae was identified in 23.2% (144/621). CAPSpn cases increased with age and the disease burden of illness was evident in terms of requirement for mechanical ventilation, intensive care unit admission, and 30-day mortality. Of serotypeable CAPSpn or IPD results, predominance for serotypes 3, 7F, 19A, and 22F was observed. The proportion of hospitalized CAP cases caused by a PCV13-type S. pneumoniae ranged between 7.0% and 14.8% among cases with at least one test for S. pneumoniae performed or in whom all four diagnostic tests were performed, respectively. Overall, vaccine-preventable pneumococcal CAP and IPD were shown to be significant causes of morbidity and mortality in hospitalized Canadian adults in the three years following infant PCV13 immunization programs in Canada.